A Network Perspective on Body Dysmorphic Disorder and Major Depressive Disorder - Summers, Berta J. (J Affect Disord, 2019)
BACKGROUND. Body dysmorphic disorder (BDD) is a highly debilitating mental disorder associated with notable psychosocial impairment and high rates of suicidality. This study investigated BDD from a network perspective, which conceptualizes mental disorders as systems of symptoms that cause and exacerbate one another (e.g., preoccupation with perceived appearance defect triggering compulsive checking in the mirror). METHODS. In a sample of BDD patients (N = 148), we used cross-sectional network models to explore the network structure of 1) BDD symptoms and 2) BDD symptoms and major depressive disorder (MDD) symptoms, and tested which symptoms were most central (i.e., most strongly associated to other symptoms). RESULTS. Interference in functioning due to appearance-related compulsions (BDD), feelings of worthlessness (MDD), and loss of pleasure (MDD) were most central. CONCLUSION. These symptoms were most strongly predictive of other BDD and MDD symptoms and may be features of BDD that warrant prioritization in theory development and treatment. A limitation of our study is that the precision of these findings may be limited due to a small sample size relative to the number of parameters. Replication studies in larger samples of BDD patients are needed.